Therapeutic and recreational methadone cardiotoxicity. (April 2016) - Lusetti, Monia; Licata, Manuela; Silingardi, Enrico; Reggiani Bonetti, Luca; Palmiere, Cristian
Abstract: Several classes of drugs have been associated with an increased risk of cardiovascular disease and occurrence of arrhythmias potentially involved in sudden deaths in chronic users even at therapeutic doses. The study presented herein focuses on pathological changes involving the heart possibly due to methadone use. 60 cases were included in the study in total and were divided into three groups (therapeutic methadone users: 20 cases, recreational methadone users: 20 cases, and sudden death group in subjects who had never taken methadone: 20 cases). Autopsies, histology, biochemistry and toxicology were performed in all cases. Macroscopic and microscopic investigation results in therapeutic methadone users were similar to those observed in sudden, unexpected deaths in non-methadone users. In recreational methadone consumers, macroscopic and microscopic examination of the heart failed to provide results consistent with acute or chronic myocardial or coronary damage, thereby corroborating the hypothesis of death most likely following respiratory depression. Highlights: Methadone blood concentrations in fatal cases are highly variable. Therapeutic doses of methadone may trigger ventricular arrhythmias. Histology in sudden death in therapeutic methadone users is often negative. Respiratory depression is responsible for the death in recreational methadone users.